Propensity score matching analysis for adverse events of EUS-guided biliary drainage in advanced elderly patients (PEACE study) - Takeshi Ogura (Therapeutic Advances in Gastroenterology, 2022)
Background: Several studies have suggested that elderly patients, as well as younger patients, can be safely treated using endoscopic retrograde cholangiopancreatography (ERCP). However, endoscopic ultrasound-guided biliary drainage (EUS-BD) has not been clinically evaluated for very elderly patients. The present multicenter, retrospective study aimed to determine the safety of EUS-BD for advanced elderly patients. Method: Patients who underwent EUS-BD during this period were retrospectively enrolled, and they were divided into two groups based on age: group A (age  < 75 years) and group B (age ⩾ 75). In this study, capnographic monitoring was used only for elderly patients (age ⩾ 75 years). Results: A total of 271 patients who underwent EUS-BD were enrolled in this study (group A = 177, group B = 94). The types of adverse events that were associated with EUS-BD was observed in 38 patients, and they did not differ significantly between two groups ( p  = 0.855). This result was confirmed after propensity score matching ( p  = 0.510). Adverse events were associated with sedation after propensity score matching; hypoxemia ( p  = 0.012) and severe hypoxemia ( p  = 0.003) were significantly higher in group A compared with group B. According to logistic regression analysis, monitoring (non-capnography) was also only risk factor (odds ratio: 0.317, 95% confidence interval: 0.143–0.705; p  = 0.005) for sedation-related adverse events. Conclusion: In conclusion, EUS-BD could be safety performed in advanced elderly patients, the same as in younger patients. Also, capnographic monitoring might be helpful in case of sedation by a gastroenterologist in a non-intubated patient. Further prospective, randomized studies are needed to confirm these conclusions.